Pendampingan Pengajuan Sertifikasi Halal Pelaku UMKM Makanan-Minuman - Rachmaniah, Orchidea; Yeni Rahmawati; Wahyu Meka; Fahmi; Nuniek Hendrianie; Ali Altway; Susianto (Universitas Muhammadiyah Malang, 2024)
Purpose – This community service activity aims to provide assistances for Small-Medium Enterprises (SMEs), specially for food and beverage field, applying halal certification via Halal self-declared (SEHATI) Program. Design/methodology/approach – This program is conducted by recruting and training students as certified halal companion (PPH) by BPJPH. This were done by collaboration between Halal Center Studies of the Institut Teknologi Sepuluh Nopember (PKH-ITS) and ITS Techno Science. The SMEs training for Halal Process held around August 2023. Afterward, all the PPH will be accompanied and assisted the SMEs for applying the halal certificate via SIHALAL system; including preparing the SJPH, entry all the information, submitting the document, verification and validation as well as done the revision untill the halal certificate was finally issued. Findings – The SEHATI program has been started since 2021 and the quota continues to increase every year. However, not every SMEs known this information. It is mandatory for food and beverage, slaughter services, and slaughter products at 17th October 2024 should be halal certified. Therefore, PKH-ITS together with PPH helps and assists SMEs in applying a halal certification through a community service program at 2022. The upgraded facilities of SIHALAL’s website (version 2022) make it more user friendly. The 15 SMEs have certified via the SEHATI22 program with PKH assistances. Originality/value – Though the SEHATI Program is announced by the goverment at 2021, this relatively not well known by the SMEs as the subject of the halal certification. Hence, third party such PKH-ITS need to present for accompanying and assisting the SMEs. The SIHALAL system is used for submitting the application of halal certification. Therefore, highly technology adapted of the PPH are required, for completely assisting the SMEs. Hence, the presence of the PPH in this process is mandatory and vital; increasing the succesibility of the SEHATI program.